Accountable leaders : inspire a culture where everyone steps up, takes ownership, and drives extraordinary results - Molinaro, Vince, 1962- (John Wiley & Sons, Inc., 2020)
"Accountable Leaders Accountable Organizations is the real-world guide to propelling your business to extraordinary levels of performance and achievement. Leadership accountability is a major issue in organizations around the globe. Research has shown that teams and individual employees are overwhelmingly dissatisfied with the degree of accountability demonstrated by their leaders. Effective teams need responsible and accountable leaders--the solution seems simple. Yet, thousands of businesses are struggling with mediocre performance and widening gaps in leadership. This essential resource provides practical and no-nonsense strategies to transform any organization into a cohesive, highly motivated culture of accountable leaders and fully committed teams"--